Perceptual Analysis of Compressed Dynamic Point Clouds in Virtual Reality Environments - Silva, Josef Augusto Oberdan Souza; Rehbein, Gustavo; Borda, Adriane; Porto, Marcelo; Corrêa, Guilherme (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This study investigated the perceived quality of dynamic point clouds in virtual reality (VR) under different compression scenarios through an immersive subjective experiment. Six compression scenarios were analyzed, including one employing a machine learning-based solution for codec complexity reduction. A VR application, developed according to ITU-T recommendations, was used to conduct the experiments and collect user scores, response times, and visual attention data. The results indicated agreement between most objective and perceived quality metrics, with moderate variability across participants. Geometric metrics, particularly p2plane and p2point, showed stronger association with MOS than bitrate and luminance PSNR, while heatmaps revealed greater gaze concentration in central and visually informative regions of the point clouds. These findings support the development of perceptually optimized compression and rendering strategies for immersive point cloud applications.